(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: The aim of this paper is to analyze overall technical efficiency (OTE), pure technical efficiency (PTE) and scale efficiency (SE) of both life and non-life insurance sectors in three Central and Eastern European countries (CEE), i.e. Croatia, Hungary and Poland, in 2018. Methodology: The efficiency of insurance sectors is estimated by applying data envelopment analysis (DEA), while a one-way analysis of variance (ANOVA) is performed to find out whether there exists any statistically significant difference between the estimated levels of the efficiency of non-life and life insurance sectors in the observed CEE countries. Results: Out of 34 non-life Polish insurers, only two (6%) were overall technically efficient, while the remaining 32 were inefficient. Croatia and Hungary achieved better results with three (20%) and seven (43.7%) efficient insurers, respectively. However, when observing the life insurance segment, half of the Croatian life insurers were efficient according to the CCR model, while six (23%) Polish and three (23%) Hungarian efficient insurers were recorded. Conclusion: Research reveals that the Hungarian non-life insurers are the most efficient ones in terms of OTE, PTE and SE. They are followed by the Croatian insurers, leaving the Polish insurers behind. Regarding the life insurance sector, the domination of the Croatian insurers is recorded, while the Hungarian ones were found to be the least efficient. Moreover, inefficiency in both life and non-life sectors (except for the Hungarian life sector) is more related to scale than to managerial inefficiency. Finally, ANOVAs and Tukey post hoc tests revealed a statistically significant difference among considered groups of insurers.